Mediating effects of meaning in life on the relationship between general self-efficacy and nursing professional commitment in nursing students: A structural equation modeling approach. Issue 29 (23rd July 2021) - Cheng, Linan; Chen, Qian; Zhang, Fengying
Abstract : Abstract: Meaning in life (MiL) is regarded as a valuable indicator of positive functioning in terms of an understanding of one's purpose in life, well-being, and professional commitment. As such, it is important to improve MiL for the stability of nursing staff. General self-efficacy is a significant predictor of both MiL and nursing professional commitment. Nursing professional commitment is key for both the stability of nursing staff and the provision of excellent health care. Few scholars have investigated the relationship between general self-efficacy and nursing professional commitment. In particular, a possible mediating effect of MiL has not been fully explored in nursing students. We aimed to examine the association between general self-efficacy and MiL among nursing students and to determine whether MiL mediates the relationship between general self-efficacy and nursing professional commitment for Chinese nursing students. A cross-sectional descriptive design was used. Between June and September 2019, 710 Chinese nursing students from 2 colleges completed the Meaning in Life Scale (MiLS), General Self-Efficacy Scale (GSES), and Nursing Professional Commitment Scale (NPCS). Data were analyzed using structural equation modeling (SEM) and SPSS (version 23.0, IBM Corp, Armonk, NY). The mean MiL score was above the moderate level ( M  = 52.55, SD = 9.79). However, the mean scores of self-efficacy and nursing professional commitment were relatively low. Self-efficacy was positively related to MiL ( B  = 0.46, P  < .01), and MiL was positively related to nursing professional commitment ( B  = 0.37, P  < .01). However, self-efficacy was not related to nursing professional commitment ( B  = 0.12, P  = .01). We therefore suggest that MiL has a complete mediating role between self-efficacy and nursing professional commitment among Chinese nursing students. In this study, we confirmed the complete mediation of nursing professional commitment by MiL in nursing students, thus providing scientific evidence that could be beneficial for the development of interventions to increase nursing professional commitment.